Kicking the Habit: The Neural Basis of Ingrained Behaviors in Cocaine Addiction - Pierce, R. Christopher (2010)
Cocaine addiction is a complex and multifaceted process encompassing a number of forms of behavioral plasticity. The process of acquiring and consuming drugs can be sufficiently risky and complicated that the casual drug user may choose not to act on every motivation to use drugs. The repetition of drug seeking and taking, however, often results in the gradual development of drug craving and compulsive drug seeking associated with addiction. Moreover, the complex sets of behaviors associated with drug addiction can become ingrained to such an extent that, when activated by drug-associated stimuli or exposure to the drug itself, the processes underlying drug seeking and taking are automatically engaged and very difficult to suppress. Here, we examine the hypothesis that aspects of cocaine seeking and taking become ingrained with repetition, thereby contributing to continued drug use despite a conscious desire to abstain. We also review emerging evidence indicating that neuronal circuits including the dorsolateral striatum play a particularly important role in the habitual aspects of drug seeking and taking.